Gender wage and productivity differentials in the Portuguese tourism industry - Mendes, Raquel (2013)
The objective of this paper is to provide empirical evidence on the determinants of gender wage inequality in the Portuguese tourism industry. Relying on firm level wage equations and production functions, gender wage and productivity differentials are estimated and then compared in order to infer whether observed gender disparities are justifiable on the grounds that women are relatively less productive than men, or instead disparities are due to gender wage discrimination. This approach is applied to tourism industry data gathered in the matched employer-employee data set Quadros de Pessoal (Employee Records). The main findings indicate that female employees in the tourism industry in Portugal are less productive than their male colleagues and that gender differences in wages are fully explained by gender differences in productivity.